2018
DOI: 10.1103/physrevb.98.104418
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic interfaces as sources of coherent spin waves

Abstract: TITLEMagnetic interfaces as sources of coherent spin waves AUTHORS Poimanov, VD; Kuchko, AN; Kruglyak, VV JOURNAL Physical Review B DEPOSITED IN OREWe have developed a simple but general analytical theory that elucidates the mechanism of spin-wave generation from interfaces between ferromagnetic media pumped by a uniform microwave magnetic field. Our calculations show that, provided there is a finite coupling between the two media, the amplitude of the emitted spin waves depends linearly on the difference betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 40 publications
(77 reference statements)
0
27
0
4
Order By: Relevance
“…We note that at μ 0 H = 0.002 T, the evaluated wavevector is still larger than expected from a nonmagnetic CPW. We attribute this observation to either the hysteresis of the Fe stripe (i.e., a finite remanent magnetization component of Fe along θ = 90°) or the differences in magnetic susceptibilities of Fe and YIG 24 . The observation of a significant wavelength-conversion process in very small applied field is promising in view of low-power consuming and compact magnonic applications, where an additional biasing magnetic field is avoided and instead electric fields control the magnonic functionality 42,43 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We note that at μ 0 H = 0.002 T, the evaluated wavevector is still larger than expected from a nonmagnetic CPW. We attribute this observation to either the hysteresis of the Fe stripe (i.e., a finite remanent magnetization component of Fe along θ = 90°) or the differences in magnetic susceptibilities of Fe and YIG 24 . The observation of a significant wavelength-conversion process in very small applied field is promising in view of low-power consuming and compact magnonic applications, where an additional biasing magnetic field is avoided and instead electric fields control the magnonic functionality 42,43 .…”
Section: Discussionmentioning
confidence: 99%
“…1b, a formalism needs to be developed, which, in the spin-precessional equation of motion, considers both the inhomogeneous effective field B eff (y) and noncollinear spin structures (Fig. 3a) as well as local differences in magnetic susceptibilities 24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of course this limitation of linear excitation may be overcome by the methods mentioned in ref. 71 . Interestingly, parametric SWs with relatively large amplitude and much narrower linewidth can be excited by VCMA 69 , as compared with Oersted field.…”
Section: Vcma-induced Ferromagnetic Resonance (Vcma-fmr)mentioning
confidence: 99%
“…Au et al have shown that localized dynamic dipolar field created by the FMR of a rod-like magnetic nanostructure on top of a SWWG can excite shorter wavelength SWs 76 . Even smooth interface between two magnetic films can also excite shortwavelength coherent SWs very efficiently 71 . All these abovementioned methods either need to create nonuniformities in magnetic film or need two magnetic layers, which may increase the complexity of device fabrication.…”
Section: Excitation Of Coherent Propagating Swsmentioning
confidence: 99%